Evidencing the Impact of Climate Change on the Phytoplankton Community of the Mediterranean Sea Through a Bioregionalization Approach. Issue 4 (17th April 2021) - El Hourany, Roy; Mejia, Carlos; Faour, Ghaleb; Crépon, Michel; Thiria, Sylvie
Abstract: We revisited the partitioning of the Mediterranean Sea into bioregions by processing satellite Sea Surface Temperature (SST) and Chlorophyll‐ a concentration (Chla) from ocean color observations combined with Argo mixed‐layer depth for a period ranging from 2003 up to 2020. This regionalization was performed using an innovative classification based on self‐organizing maps, the so‐called 2S‐SOM. We clustered the Mediterranean Sea waters into seven bioregions governed by specific physical and biogeochemical characteristics. We studied the interannual variability of these bioregions over the 18 years. We showed that the temperature is increasing with a mean rate of 0.4°C per decade. The chlorophyll‐ a concentration is quasi constant, but we evidenced a noticeable change in satellite‐derived phytoplankton communities: Diatoms concentration is decreasing while cyanobacteria concentration is increasing. The bioregion trends could be related to global warming. The whole Mediterranean Sea is shifting to an eastern Mediterranean state. Plain Language Summary: The Mediterranean is a miniature ocean where most of the processes documented in the global ocean are encountered. At a regional scale, the Mediterranean Sea plays a role of sentinel with regards to global warming. Indeed, the Mediterranean Sea has shown a warming trend throughout several studies, but the primary production seems to be stable. In this study, we propose a new decomposition of the surface Mediterranean waters into bioregions based on a neural network classifier applied to satellite and Argo‐float observations. The resultant bioregionalization shows a significant interannual variability and trends that coincide with the warming of the basin. Using satellite estimates of Phytoplankton groups, show significant changes in the phytoplankton community composition in every bioregion throughout the 18 years studied period. The bioregion trends could be related to global warming. Key Points: The Mediterranean Sea is partitioned in seven bioregions with a neural classifier using satellite Sea Surface Temperature and chlorophyll‐ a concentration (Chla) and mixed‐layer depth Argo‐float data Temperature is increasing while the Chla concentration remains constant through the 18 years studied period for each bioregion Satellite estimates show that diatom and nanoplankton dominance is decreasing while cyanobacteria are increasing during the 18 studied years